Mapping midwifery and obstetric units in England - Walsh, Denis; Spiby, Helen; Grigg, Celia P.; Dodwell, Miranda; McCourt, Christine; Culley, Lorraine; Bishop, Simon; Wilkinson, Jane; Coleby, Dawn; Pacanowski, Lynne; Thornton, Jim; Byers, Sonia (Elsevier, 2017)
Objective: to describe the configuration of midwifery units, both alongside&free-standing, and obstetric units in England. Design: national survey amongst Heads of Midwifery in English Maternity Services Setting: National Health Service (NHS) in England Participants: English Maternity Services Measurements: descriptive statistics of Alongside Midwifery Units and Free-standing Midwifery Units and Obstetric Units and their annual births/year in English Maternity Services Findings: alongside midwifery units have nearly doubled since 2010 (n = 53–97); free-standing midwifery units have increased slightly (n = 58–61). There has been a significant reduction in maternity services without either an alongside or free-standing midwifery unit (75–32). The percentage of all births in midwifery units has trebled, now representing 14% of all births in England. This masks significant differences in percentage of all births in midwifery units between different maternity services with a spread of 4% to 31%. Key conclusions: In some areas of England, women have no access to a local midwifery unit, despite the National Institute for Health&Clinical Excellence (NICE) recommending them as an important place of birth option for low risk women. The numbers of midwifery units have increased significantly in England since 2010 but this growth is almost exclusively in alongside midwifery units. The percentage of women giving birth in midwifery units varies significantly between maternity services suggesting that many midwifery units are underutilised. Implications for practice: Both the availability and utilisation of midwifery units in England could be improved.